2011
DOI: 10.1371/journal.pgen.1002295
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of QTLs and Genes Altering Natural Variation in Stochastic Noise

Abstract: Quantitative genetic analysis has long been used to study how natural variation of genotype can influence an organism's phenotype. While most studies have focused on genetic determinants of phenotypic average, it is rapidly becoming understood that stochastic noise is genetically determined. However, it is not known how many traits display genetic control of stochastic noise nor how broadly these stochastic loci are distributed within the genome. Understanding these questions is critical to our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 120 publications
(227 reference statements)
5
113
0
Order By: Relevance
“…The high-resolution nature of the BILs, along with the fact that the genomes of both parental lines have been sequenced (Bolger et al, 2014), rendered it possible to obtain relatively short gene lists for the nine regions that we used for validation via the independent population (Supplemental Data Set 14). Interestingly, several of the genes contained within the cross-validated intervals are associated with regulatory proteins, including those encoding chaperones, receptor-like kinases, and transcription factors (see Supplemental Files 1 and 2 for a detailed discussion) and as such are similar to previously described genes associated with canalization of developmental phenotypes in both plants (Queitsch et al, 2002;Hall et al, 2007;Jimenez-Gomez et al, 2011) and other biological systems (Rutherford and Lindquist, 1998;Specchia et al, 2010).…”
Section: Validation Of Identified Cmqtl With the Solanum Pennellii Bimentioning
confidence: 65%
“…The high-resolution nature of the BILs, along with the fact that the genomes of both parental lines have been sequenced (Bolger et al, 2014), rendered it possible to obtain relatively short gene lists for the nine regions that we used for validation via the independent population (Supplemental Data Set 14). Interestingly, several of the genes contained within the cross-validated intervals are associated with regulatory proteins, including those encoding chaperones, receptor-like kinases, and transcription factors (see Supplemental Files 1 and 2 for a detailed discussion) and as such are similar to previously described genes associated with canalization of developmental phenotypes in both plants (Queitsch et al, 2002;Hall et al, 2007;Jimenez-Gomez et al, 2011) and other biological systems (Rutherford and Lindquist, 1998;Specchia et al, 2010).…”
Section: Validation Of Identified Cmqtl With the Solanum Pennellii Bimentioning
confidence: 65%
“…There is empirical evidence across several species that the variance among phenotypes is genotype dependent (Ansel et al 2008;Wolc et al 2009;Hill and Mulder 2010;Jimenez-Gomez et al 2011). Understanding genetic control of phenotypic variability has become increasingly important in evolutionary biology, human medicine, the agricultural industry and other branches of biological science (Gibson 2009;Yang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are more recent data on genetic control of V E at the level of individual loci from genome-wide association studies (see review by GeilerSamerotte et al 2013). Those in experimental species are very clear cut: for example, Jimenez-Gomez et al (2011) and Nelson et al (2013) located QTL for phenotypic variability in gene expression in Arabidopsis and yeast, respectively, and Shen et al (2012) identified regions controlling the phenotypic variability of traits in Arabidopsis. In vertebrates, the FTO genotype was shown to be associated with phenotypic variability in body mass index in humans, with the two homozygotes differing 7% in standard deviation (SD) (Yang et al 2012).…”
mentioning
confidence: 99%